The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1371/journal.pone.0248281
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of COVID-19 patients with comorbidities in southwest Nigeria

Abstract: Background Data on the comorbidities that result in negative outcomes for people with COVID-19 are currently scarce for African populations. This study identifies comorbidities that predict death among a large sample of COVID-19 patients from Nigeria. Methods This was a retrospective analysis of medical records for 2184 laboratory confirmed cases of COVID-19 in Lagos, southwest Nigeria. Extracted data included age, sex, severity of condition at presentation and self-reported comorbidities. The outcomes of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
66
4
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(103 citation statements)
references
References 34 publications
(48 reference statements)
18
66
4
6
Order By: Relevance
“…More middle-aged persons were affected by covid-19 with a Mean age (SD) of 44.5±34.5. This is in line with similar articles from Nigeria, with a mean age of 46.16 and a median age of 43 years (IQR: 33-55) [4].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…More middle-aged persons were affected by covid-19 with a Mean age (SD) of 44.5±34.5. This is in line with similar articles from Nigeria, with a mean age of 46.16 and a median age of 43 years (IQR: 33-55) [4].…”
Section: Discussionsupporting
confidence: 92%
“…This study comprised 327 admitted patients in an isolation center in South-South Nigeria, 215 (63.2%) were males and 112 were females (36.8%). Similar studies in South-Western Nigeria showed 74.7% male preponderance [12] and 65.8% male [4]. Global data indicated a higher covid-19 case fatality rate among men than women [13].…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations